การกำหนดกลยุทธ์ระดับธุรกิจสำหรับการผลิตน้ำมันหล่อลื่นเครื่องยนต์ - ศิวพงศ์ กุศลภุชฌงค์ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The aim of this thesis is to analyse the external environment and the internal environment and develop the business strategy for manufacturing of engine oil. The plant of the company is located in PathumThani, and another company that is responsible for marketing and sales of this product is located in Bangkok. The research methodology consists of : 1. Studying and collecting the information from the company, customers and outside information sources 2. Analysing the external environment and the internal environment by using strategic planning 3. Using the Analytic Hierarchy Process as a decision making tool for determining the best strategy by Managing Director and Plant Manager. The main criteria for determining the best strategy consist of : 1. objectives 2. strengths 3. weaknesses 4. opportunities 5. threats and 6. key success factors. The generic competitive strategies consist of : 1. Overall Low-Cost Leadership Strategy 2. Broad Differentiation Strategy 3. Best-Cost Provider Strategy 4. Focused Low-Cost Strategy and 5. Focused Differentiation Strategy. The research results indicate that the most important criterion for determining the best strategy is Strength, and the best competitive strategy for this company is Best-Cost Provider Strategy.